Are you a die-hard K-pop fan? Examining English Korean code mixing uttered by an American native speaker youtuber - Khadijah Khadijah; Emy Sudarwati (Journal of Applied Linguistics and Literature, 2022)
This study analyzes the types and reasons for code-mixing used by the speaker with a concern for the interlocutors, who are a native speaker and a non-native speaker. The significance of comparing the speaker's code-mixing aims to know if changes in the interlocutors affect the types and reasons for code-mixing adopted. This analysis applied the qualitative descriptive method to analyze data taken from two YouTube videos of an American native speaker namely Edward Avila entitled Chopping all my friend’s hair off and giving him makeover with Korean native speaker as the interlocutor and catching up with Sorn + A soft glam lewk with Korean non-native speaker as the interlocutor. For Korean native speaker interlocutor, the most frequently used code-mixing type is alternation, while for Korean non-native speaker interlocutor is insertion. However, the data identified three specific reasons for code-mixing with Korean native speaker interlocutor, notably clarification of the speech content, interjection, and quotation of someone else. Meanwhile, there are two specific causes for code-mixing revealed in the data of Korean non-native speaker interlocutor, namely discussion of a specific topic and repetition used for clarification. The varied types of interlocutors had an impact on the forms of code-mixing and the reasons for code-mixing in the dialogue